[OP.3B.07] ARTERIAL HYPERTENSION AS PROGNOSTIC MARKER IN PATIENTS WITH ST-ELEVATION MYOCARDIAL INFARCTION AND EARLY PERCUTANEOUS CORONARY INTERVENTION. (September 2017) - Reuter, H.; Hoffmann, F.; Zander, W.O.; Ulbrich, L.; Baldus, S.; Halbach, M.
Abstract : Objective: Strong evidence points to the prognostic value of renin-angiotensin-system (RAS)-inhibitors (ACE inhibitors or AT1-receptor blockers) and beta blockers (BB) in the secondary prevention after myocardial infarction (MI). However, adequate dosing of these drugs is often limited due to their blood pressure lowering effects, especially early after MI. The present study therefore sought to identify differences in rates of prescription, persistence and dosing of RAS-inhibitors and BB early after acute ST-elevation MI (STEMI) and its impact on survival in hypertensive and non-hypertensive patients. Design and method: 1003 consecutive patients with adjudicated STEMI treated by early percutaneous coronary intervention (PCI) between 2007 and 2011 in a single centre were retrospectively dichotomized according to their history of arterial hypertension at the time of hospital admission. Results: Mean age was 63 ± 13 years, body mass index 27 ± 5 kg/m 2, 24% were women. 749 patients were diagnosed with hypertension. Mortality was 11.3% at 30 days and 17.2% at 1 year follow-up. History of hypertension at time of hospital admission was significantly associated with lower mortality on follow-up (OR, at 30 days: 0.41 (0.27–0.64), at 1 year 0.37 (0.26–0.53)). Persistence to RAS-inhibitors was significantly higher in hypertensive patients compared to non-hypertensives (84% vs. 70%, p = 0.004). However, persistence to BB did not differ between groups (88% vs 86%, n.s.). At discharge the rate of prescription of RAS-inhibitors and BB was significantly higher in hypertensive patients (RAS-inhibitors: 87.3% vs. 69.8%, p < 0.001; BB: 92.8% vs. 84.3%, p < 0.001). In addition, the defined daily dose (DDD) among patients receiving RAS-inhibitors at discharge was higher in hypertensive versus non-hypertensive patients (DDD: 0.40 vs. 0.30, p < 0.001), whereas there was no difference for BB. At 30 days and 1 year follow-up survival was significantly associated with the prescription of RAS-inhibitors as well as BB at discharge. Conclusions: Patients with a history of hypertension show higher prescription rates at discharge, better long-term persistence as well as higher individual dosing of RAS-inhibitors after STEMI. This, as well as the higher prescription rates of BB, may contribute to the better survival that we observed in patients with history of hypertension compared to non-hypertensive controls.